Personalized Radiation Attenuating Materials for Gastrointestinal Mucosal Protection. Issue 12 (27th April 2021) - Byrne, James D.; Young, Cameron C.; Chu, Jacqueline N.; Pursley, Jennifer; Chen, Mu Xian; Wentworth, Adam J.; Feng, Annie; Kirtane, Ameya R.; Remillard, Kyla A.; Hancox, Cindy I.; Bhagwat, Mandar S.; Machado, Nicole; et al.
Abstract: Cancer patients undergoing therapeutic radiation routinely develop injury of the adjacent gastrointestinal (GI) tract mucosa due to treatment. To reduce radiation dose to critical GI structures including the rectum and oral mucosa, 3D‐printed GI radioprotective devices composed of high‐Z materials are generated from patient CT scans. In a radiation proctitis rat model, a significant reduction in crypt injury is demonstrated with the device compared to without ( p < 0.0087). Optimal device placement for radiation attenuation is further confirmed in a swine model. Dosimetric modeling in oral cavity cancer patients demonstrates a 30% radiation dose reduction to the normal buccal mucosa and a 15.2% dose reduction in the rectum for prostate cancer patients with the radioprotectant material in place compared to without. Finally, it is found that the rectal radioprotectant device is more cost‐effective compared to a hydrogel rectal spacer. Taken together, these data suggest that personalized radioprotectant devices may be used to reduce GI tissue injury in cancer patients undergoing therapeutic radiation. Abstract : One of the most common side effects of radiation therapy is injury to the gastrointestinal (GI) tract. To reduce radiation‐induced injury, personalized 3D‐printed radioprotective devices made of high‐Z materials are developed that are shown to reduce radiation injury in two animal models, improve clinically significant dosimetry in at‐risk GI tissue in human cancer patients, and are more cost‐effective compared to standard‐of‐care therapy.